2014
DOI: 10.4236/ojvm.2014.49022
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Lesions, Obesity, and Mesenteric Lipomas in Insulin-Resistant Horses

Abstract: The aim of the current study was to identify associations between pituitary lesions, body condition scores, and mesenteric lipomas in horses with insulin resistance. Necropsy examinations were performed following euthanasia in 30 adult horses designated as insulin resistant (n = 11) or insulin sensitive (n = 19). Insulin sensitivity was determined using the insulin-modified frequently sampled intravenous glucose tolerance test and resting insulin concentrations. At necropsy, mesenteric lipomas were measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…A B Although no scientific evidence of the association between obesity and pedunculated lipoma has been proven, Frank [6] has observed that pedunculated lipomas are more common in horses with metabolic alterations. Another author also found a higher frequency of this disease in horses presenting insulin resistance and diffuse pars intermedia hyperplasia [14]. The mare reported in this study had a high BCS, however no metabolic profile was performed.…”
Section: Discussionsupporting
confidence: 58%
“…A B Although no scientific evidence of the association between obesity and pedunculated lipoma has been proven, Frank [6] has observed that pedunculated lipomas are more common in horses with metabolic alterations. Another author also found a higher frequency of this disease in horses presenting insulin resistance and diffuse pars intermedia hyperplasia [14]. The mare reported in this study had a high BCS, however no metabolic profile was performed.…”
Section: Discussionsupporting
confidence: 58%
“…Abnormal ultrasound appearance of the mesenteric fat has also been described in some inflammatory bowel condition such as Crohn's disease (Maconi et al, 2008). To the authors' knowledge, there is no currently published evidence of a clear link between obesity/increased body mass and increased risk of abdominal lipoma/lipomatosis in horses (Newkirk et al, 2014). However, in the aforementioned study, insulin‐resistant horses and horses with diffuse pituitary hyperplasia (both more likely to suffer from endocrinopathies) were more likely to have incidental lipomas detected on post‐mortem examination compared with controls, and further research is required in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal ultrasound appearance of the mesenteric fat has also been described in some inflammatory bowel condition such as Crohn's disease (Maconi et al, 2008). To the authors' knowledge, there is no currently published evidence of a clear link between obesity/increased body mass and increased risk of abdominal lipoma/lipomatosis in horses (Newkirk et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted to assess the short-term survival rate of colic in a group of 300 horses and ponies that underwent exploratory laparotomy identified that 13% of those animals required surgical intervention due to intestinal strangulation by pedunculated lipoma, and the short-term survival rate of those 39 animals was 64.1% [ 43 ]. Interestingly, a recent study that evaluated associations between pituitary lesions, obesity and the presence of mesenteric lipomas in insulin-resistant horses found that whilst insulin-resistant horses had a higher frequency of mesenteric lipomas, there was no association between obesity and the frequency of mesenteric lipomas [ 44 ]. This finding combined with our finding in the current study that mesenteric fat scores were not associated with BCS would perhaps suggest that mesenteric fat scores as opposed to BCS may be associated with the frequency of mesenteric lipomas and may be an area for future study.…”
Section: Discussionmentioning
confidence: 99%